Discrete copper(ii)-formate complexes as catalytic precursors for photo-induced reversible deactivation polymerization. Issue 1 (29th October 2015) - Nikolaou, Vasiliki; Anastasaki, Athina; Brandford-Adams, Francesca; Whitfield, Richard; Jones, Glen R.; Nurumbetov, Gabit; Haddleton, David M.
Abstract : Traditional copper-mediated reversible deactivation polymerization techniques (RDRP) employ various components mixed in situ ( e.g. ligand, metal salt, additional deactivation species etc .) in order to achieve good control over the molecular weight distributions. Abstract : Traditional copper-mediated reversible deactivation polymerization techniques (RDRP) employ various components mixed in situ ( e.g. ligand, metal salt, additional deactivation species etc .) in order to achieve good control over the molecular weight distributions. In a previous communication we described a discrete copper(ii )-formate/Me6 -Tren complex to catalyse the polymerization of acrylates. Herein, we expand the scope of this complex by investigating the compatibility with various solvents, including acetonitrile (MeCN), dimethylformamide (DMF), methanol (MeOH), isopropanol (IPA), toluene, 2, 2, 2-trifluoroethanol (TFE) and water as well as mixtures thereof. A series of both hydrophilic and hydrophobic acrylic monomers are reported including n and tert butyl acrylate ( n -BA and t -BA), poly ethylene glycol acrylate (PEGA), diethylene glycol ethyl ether acrylate (DEGEEA), lauryl acrylate (LA), octadecyl acrylate (ODA), hydroxyethyl acrylate (HEA), hydroxyl propyl acrylate (HPA) and solketal acrylate (SA). In most cases, narrow molecular weight distributions were attained (typically < 1.20), even when the polymerization was allowed to reach high conversions (>95%). High molecular weight polymers were targeted achieving poly(MA) with a final dispersity of 1.12 within 2 h ( M n ∼ 120 000 g mol −1 ) with additional NaBr being essential to obtain even higher molecular weight polymers. As Me6 -Tren is relatively expensive to purchase commercially, an additional PMDETA complex was also synthesized, allowing for the polymerization of methacrylates ( e.g. MMA) in addition to the polymerization of acrylates. Narrow molecular weight distributions, high monomer conversion and good spatiotemporal control could be achieved with this complex, demonstrating that it could be an efficient and less expensive alternative to obtain well-defined poly(acrylates) and poly(methacrylates).